2020
DOI: 10.1016/j.jcou.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural modifications of calcium based catalysts by non-thermal plasma in the CO2 reforming of CH4 and the influence of water

Abstract: Calcium oxide, calcium hydroxide and calcium carbonate were tested for the CO2/CH4 reaction in a dielectric barrier discharge plasma reactor under humid conditions. It appeared that the presence of water in the gas stream enhanced slightly the selectivity to CO and H2 syngas on each support (2 to 5 %), contrary to the selectivities to CxHy that decreased (0.5 to 2 %). The water showed little effect on oxygenates selectivities (in the order of 0.1%) compared to dry treatment. The three materials were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Some studies have shown that the presence of water with calcium oxide can help improve the conversion of carbon dioxide in the non-thermal plasma process from 11.3% to 14.7% at room temperature. The selectivity of methanol, ethanol, acetaldehyde, and acetone increased from 1.0%, 0.3%, 0.3%, 0.4% to 1.4%, 0.5%, 1.1%, and 0.7%, respectively [130].…”
Section: Carbon Dioxide Conversion By Plasma Catalysismentioning
confidence: 92%
“…Some studies have shown that the presence of water with calcium oxide can help improve the conversion of carbon dioxide in the non-thermal plasma process from 11.3% to 14.7% at room temperature. The selectivity of methanol, ethanol, acetaldehyde, and acetone increased from 1.0%, 0.3%, 0.3%, 0.4% to 1.4%, 0.5%, 1.1%, and 0.7%, respectively [130].…”
Section: Carbon Dioxide Conversion By Plasma Catalysismentioning
confidence: 92%
“…Bouchoul et al [130] tested three different calcium-based materials for CO 2 /CH 4 reforming in a DBD plasma reactor with and without the addition of water; the chosen input power (8 W) excluded the thermal activation of reactants. It was observed that reactants conversion was not significantly influenced by the nature of the Ca-based material, and the only detected difference was a lower formation of formaldehyde in presence of CaO.…”
Section: Co2 Reforming Of Methanementioning
confidence: 99%
“…The reforming of CH 4 with CO 2 , also designated as the dry reforming of methane (DRM), was regarded as an attractive pathway for the conversion of GHGs into syngas (i.e., H 2 + CO). Syngas is an important intermediate for the synthesis of various chemicals and fuels, such as ammonia, methanol, and dimethyl ether (DME) (Bouchoul et al, 2020;Cao et al, 2018;Vakili et al, 2020). Despite the optimization of reforming conditions, such as temperature, the composition of the reactant gas, space velocity, and pressure, there had been great efforts to reduce the energy consumption associated with DRM due to the high endothermicity of the reaction.…”
Section: Introductionmentioning
confidence: 99%